Evaluation of physical and chemical parameters of sea water in the surroundings of Uvita Island, Limon, Costa Rica - Alfaro-Sandí, Jaime (2021)
The present work evaluated a series of physical and chemical parameters to determine the quality of marine water in the surroundings of Uvita island, Limón, Costa Rica, and to determine the possible influence of the discharges coming from the submarine emissary of the city of Limón on the surrounding marine environment. Nutrients (nitrites, nitrates, silicates, phosphates and ammonium), heavy metals (lead, chromium, nickel), solids (dissolved and sedimentable) and physical parameters (pH, temperature, turbidity, etc.) were evaluated. The study area was divided into segments surrounding Uvita island, and 6 sampling points were located around the island in order to compare the water quality of the areas with greater emissary influence with those of less influence. Three sampling activities were scheduled: September 2012 (rainy season), october 2012 (rainy-dry transition) and september 2013 (rainy season). The levels of nutrients, heavy metals, solids and physical parameters were compared with those reported in the literature for the Gulf of Mexico and the Caribbean Sea, finding that, in general, they were higher than those reported in the literature. In particular, the last sampling data showed a considerable increase in the concentration of the heavy metals (Pb, Cr and Ni), which could be attributed to other factors outside the emissary’s discharges such as port operations and industrial anthropogenic activities, which impact on the aforementioned area.